The Wiley-Blackwell handbook of individual differences - Chamorro-Premuzic, Tomas; Von Stumm, Sophie; Furnham, Adrian (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2011)
'The Wiley-Blackwell Handbook of Individual Differences provides a comprehensive, up-to-date overview of recent research, current perspectives, practical applications, and likely future developments in individual differences. Brings together the work of the top global researchers within the area of individual differences, including Philip L. Ackerman, Ian J. Deary, Ed Diener, Robert Hogan, Deniz S. Ones and Dean Keith Simonton. Covers methodological, theoretical and paradigm changes in the area of individual differences. Individual chapters cover core areas of individual differences including personality and intelligence, biological causes of individual differences, and creativity and emotional intelligence'--
'The Wiley-Blackwell Handbook of Individual Differences provides a comprehensive, up-to-date overview of recent research, current perspectives, practical applications, and likely future developments in the field of individual differences. Bringing together the work of top researchers in the field from around the world, this essential reference work covers methodological, theoretical, and paradigm changes in the area of individual differences. Separate chapters cover core areas of individual differences including personality and intelligence, biological causes of individual differences, and creativity and emotional intelligence. The unparalleled scope of this work makes it a must-have resource for advanced psychology students, academics, and practitioners'--
Machine generated contents note: Preface. -- Section I Individual differences: An up-to-date historical and methodological overview. -- Chapter 1 Individual Differences and Differential Psychology: A brief history and prospect (William Revelle, David M. Condon, and Joshua Wilt) -- Chapter 2 Methodological Advances in Differential Psychology (William Revelle, David M. Condon, and Joshua Wilt). -- Section II Intelligence and Personality: Structure and Development -- Part 1 Personality -- Chapter 3 Personality Development Across the Life Span (Jaap J.A. Denissen, Marcel A.G. van Aken, and Brent W. Roberts). -- Chapter 4 Reinforcement Sensitivity Theory, Research, Applications and Future (Luke D. Smillie, Natalie J. Loxton, and Rachel E. Avery). -- Chapter 5 The General Factor of Personality: Normal and Abnormal (J. Philippe Rushton and Paul Irwing). -- Chapter 6 Five Into One Doesn't Go: A Critique of the General Factor of Personality (Eamonn Ferguson, Tomas Chamorro-Premuzic, Alan Pickering, and Alexander Weiss). -- Part 2 Intelligence -- Chapter 7 The Nature and Structure of'Intelligence' Charlie L. Reeve & Silvia Bonaccio). -- Chapter 8 Re-visiting Intelligence-Personality Associations: Vindicating Intellectual Investment (Sophie von Stumm, Tomas Chamorro-Premuzic, and Philip L. Ackerman). -- Chapter 9 Individual Differences in Cognitive Aging (Elliot M. Tucker-Drob, and Timothy A. Salthouse). -- Section III Biological Causes of Individual Differences -- Chapter 10 Behavior Genetics (Frank M. Spinath and Wendy Johnson). -- Chapter 11 Molecular Genetic Aspects of Personality (Alexander Strobel and Burkhard Brocke). -- Chapter 12 Understanding Human Intelligence Imaging the Brain (Roberto Colom and Paul M. Thompson). -- Chapter 13 Evolutionary psychology and individual differences (Satoshi Kanazawa). -- Section IV Individual Differences and real-world outcomes -- Part 1 Work -- Chapter 14 Individual Differences at Work (Deniz S. Ones and Chockalingam Viswesvaran). -- Chapter 15 Leadership (Robert Hogan and Ghufran Ahmad). -- Part 2 Health, Longevity and Death -- Chapter 16 Cognitive Epidemiology: concepts, evidence, and future directions (Catherine M. Calvin, G. David Batty, and Ian J. Deary). -- Chapter 17 Personality and Differences in Health and Longevity (Margaret L. Kern and Howard S. Friedman). -- Part 3 Society -- Chapter 18 Personality and the laws of history (Robert Hogan & Tomas Chamorro-Premuzic). -- Chapter 19 Individual differences and antisocial behaviour. (Vincent Egan). -- Chapter 20 & Intelligence and Social Inequality: Why the Biological Link? (Linda S. Gottfredson). -- Section V Motivation and Vocational Interests -- Chapter 21 Goal Setting: A State Theory but Related to Traits (Gary P. Latham, Deshani B. Ganegoda, and Edwin A. Locke). -- Chapter 22 Personality and Approaches to Learning (Adrian Furnham). -- Chapter 23 Vocational Interests: The Road Less Traveled (Patrick Ian Armstrong, Rong Su, and James Rounds). -- Section VI Competence beyond IQ -- Part 1 Special Abilities -- Chapter 24 Exceptional Talent and Genius (Dean Keith Simonton). -- Chapter 25 Emotional Intelligence(K.V. Petrides). -- Chapter 26 Individual Differences in Creativity (James C. Kaufman). -- Part 2 Relationships and Subjective Well-being -- Chapter 27 Personality and Happiness: Predicting the Experience of Subjective Well-Being (William Pavot and Ed Diener). -- Chapter 28 Self-Esteem: Enduring Issues and Controversies (M. Brent Donnellan, Kali H. Trzesniewski, and Richard W. Robins). -- Chapter 29 Love at first sight? Individual differences and the psychology of initial romantic attraction (Viren Swami). -- Chapter 30 Manifestations of Individual Differences in Physical and Virtual Environments(Lindsay T. Graham, Carson J. Sandy, and Samuel D. Gosling).
Includes bibliographical references and index.
Keywords: Individual differences -- Handbooks, manuals, etc; Personality -- Handbooks, manuals, etc; Intellect -- Handbooks, manuals, etc; PSYCHOLOGY -- Personality; Individual differences; Intellect; Personality; Electronic books; Handbooks and manuals